D.J. and the Zulu parade - McConduit, Denise Walter; Henriquez, Emile F.; Barbarin, Lucien C. (Gretna : Pelican, 1995)
On Mardi Gras seven-year-old D.J. experiences the excitement of being a page to the queen in the Zulu parade, the oldest black parade in New Orleans.
3.5
K-3
Keywords: Mardi Gras -- Fiction; New Orleans (La.) -- Fiction; Parades -- Fiction; Afro-Americans -- Fiction; New Orleans (La.) -- Fiction; Parades -- Fiction; Carnival -- Fiction; African Americans -- Fiction